An appraisal of the agricultural credit situation in Barangay Gacao, Palo, Leyte - Navarrete, Ma. Luz P.; Repulda, Rosalinda (Tacloban City Ma. Luz P. Navarrete, 1979)
To boost agricultural production and subsequently to raise farm incomes and upgrade living standard, problems of credit extension must be dealt with effectively. To this end, this study aims to provide credit agencies, students, etc., insights on the actual credit situations and experiences of farmers.
The study has the following specific objectives: 1. to study the actual use of farm credit of farmers in Barangay Gacao, Palo; 2. to evaluate the impact of agricultural credit on farm production among farmer-borrowers; 3. to analyze the causes and extent of agricultural credit non-repayment and the causal factors attendant to it; 4. to determine the technological and attitudinal effects of credit extensions; and 5. to know the respondents' own evaluation of the different lending indtitutions.
The population of the study includes all farmer-borrowers. Among the 135 farmers in the barangay, 26 or 19 percent were loan recipients of Masagana-99 and 45 or 1/3 were borrowers of RP-Japan Food Production Program.
Accidental sampling was used and 50 sample farmer-borrowers were interviewed at random.
The loans were purely for palay, since most of the farmers were affiliated with Masagana-99.
Throughout the reference period of the study, (November, 1975 to April, 1979), there was a 2 percent diversion or misapplication of borrowed funds.
Although the increase in productivity reported (1 respondent) was as high as 66 cavans per hectare, there were reports that productivity decreased by as much as 20 cavans per hectare (3 respondents).
About 84 percent of the respondents attributed non-repayment to low production due to misappropriation of loans. Other causes cited for non-repayment include crop failure due to rice pests, diseases, natural calamity (48 percent), yield just enough for subsistence (34 percent), habit of not paying loans (32 percent), crop failure due to negligence on the part of the farmer (20 percent), several loan obligations of farmers (12 farmers), amount of loan exceed the capability to pay (4 percent), farmers want coselda members to repay before they will repay (2 percent) and dole-out mentality (2 percent).
Among the sources of loans, Masagana-99 granted the greatest volume of loan (51 percent), RP-Japan Food Production Program granted 14 percent of the total loans, the rice future credit system accounted for 14 percent, private lenders extended 11 percent of the total amount, while Rural Bank of Palo accounted for 10 percent. Loans aggregated amounted to Php. 56, 757.59.
Throughout the reference period about 59 percent of the total loans extended remained unpaid. However, 18 percent of these represented balances of those who had made partial payments.
Ninety percent indicated increased farm production and income as direct benefits derived from loans, 56 percent used loan as payment for hired labor, 50 percent procured needed farm inputs, 26 percent stated that credit helped met household needs, 20 percent procured tools and equipment out of the borrowed capital, and 8 percent used loans as payment of previous debts.
On the other hand, 2 percent of the farmers interviewed considered the loan ineffective.
Of the farmers interviewed, the response to Masagana-99 production program in terms of affiliation was loan (34 percent). Similarly, only 16 percent were members of the Philippine Farmers Association. More than half (58 percent) were non-participants of any food production program.
Most of the respondents like the palangoy system because it is immediately available as the need arises (24), no loan collateral is needed (11), no paper works (6), low interest rate (5), repayment period can be extended (5), and because it provides small loans for consumption (3).
On the other hand, a considerable number (19), do not like its high interest rate, the unscrupulous insistence of some lenders on prompt repayment (4), and the partiality of some lenders (3).
Similarly, most of the respondents like to avail of RP-Japan Food Production Program fertilizer loans because of its low interest rate (23), available technical assistance in farm management (18), timeliness of release (18), no loan collateral (17), they can avail of the needed fertlizer if they are short of cash (3), the loan period is appropriate (2) and the technician is easy to contact (2).
Among the weak points of the program are the lack or shortage of fertilizers supply at times (3), the great distance of fertilizer supply (1) and the inavailability of cash credit (1).
On Masagana-99 most of the respondents find some strong points on its financing scheme. According to them, M-99 provides complete farm inputs plus cash (7), it has low interest rate (7), timely release of loan (7), no loan collateral (5), it provides technical assistance (4), loans can be paid in installments (2) and members can reloan if able to repay (1).
Some weak points of Masagana-99 mentioned by the respondents are the ineffective selda agreement (1), inadequate budget for one hectare (1) and high service fee plus interest rate (1).
Similarly, the respondents find more good points in the lending practices of Rural Bank of Palo such as the low interest rate (4), its nearness (2), immediate release of loan (2), few paper works (2), appropriate loan period (1) and the payment of interest in advance, lightening the total loan obligation (1).
Only one respondent noticed partiality of Rural Bank of Palo personnels and another mentioned red tape in loan processing.
Prices received by most of the sample farmers were below the price support of 1978 (Php 1.10 per kilo or Php 48.40 per cavan. Out of the 50 sample-borrowers, 96 percent (48) were receiving prices below the price support level.